2016
DOI: 10.1038/oncsis.2016.58
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma-binding protein 2 (RBP2) is frequently expressed in neuroendocrine tumors and promotes the neoplastic phenotype

Abstract: Neuroendocrine tumors (NETs), which can have survival rates as low as 4%, currently have limited therapeutic interventions available highlighting the dire need for the identification of novel biological targets for use as new potential drug targets. One such potential target is retinoblastoma-binding protein 2 (RBP2), an H3K4 demethylase whose overexpression has been linked to cancer formation and metastasis in non-endocrine tumor types. We measured RBP2 mRNA and protein levels in enteropancreatic NETs by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…However, JIB-04 also leads to increased CDKN1A levels in p53-mutant A673 cells (Figures 3B and 6B ), which, notably, do not induce CDKN1A in response to the DNA-damaging agent etoposide [ 42 ]. CDKN1A levels can additionally be subject to control by modulation of H3K4 methylation levels [ 43 , 44 ]. To determine whether the latter mechanism could be contributing to induction of CDKN1A expression in A673 cells, we examined H3K4 methylation at the CDKN1A promoter by ChIP-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…However, JIB-04 also leads to increased CDKN1A levels in p53-mutant A673 cells (Figures 3B and 6B ), which, notably, do not induce CDKN1A in response to the DNA-damaging agent etoposide [ 42 ]. CDKN1A levels can additionally be subject to control by modulation of H3K4 methylation levels [ 43 , 44 ]. To determine whether the latter mechanism could be contributing to induction of CDKN1A expression in A673 cells, we examined H3K4 methylation at the CDKN1A promoter by ChIP-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…There is mounting evidence that supports a critical role for RBP2 in a variety of tumors, including neuroendocrine tumors. For example, Maggi et al (27) recently reported that RBP2 is overexpressed in neuroendocrine tumors of diverse origin and that siRNA-mediated inhibition of RBP2 suppressed the proliferation, migration, and invasion of pancreatic and lung neuroendocrine cancer cell lines. Moreover, our group showed that germline inactivation of Rbp2 caused a significant delay in the development of mouse neuroendocrine tumors linked to Rb1 or Men1 deletion (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RBP2's ability to promote expression of the metastasisassociated gene TNC (encoding tenascin C) and to promote invasion of the metastatic LM2 breast cancer cell line is not attenuated by an RBP2 missense mutation, H483A, that abrogates RBP2's demethylase activity (21,24). Likewise, overexpression of the RBP2 H483A mutant stimulates migration, invasion, and anchorage-independent growth of immortalized pancreatic islet cells in a manner indistinguishable from the wild-type protein (27). A caveat to such overexpression studies is that RBP2 contains the LXCXE motif that was first found in the SV40 large T, adenovirus E1A, and human papillomavirus E7 oncoproteins and might, accordingly, sequester a number of cellular proteins when overexpressed, including other members of the pRB family.…”
Section: Discussionmentioning
confidence: 99%
“…In ileal NENs, the low or absent expression of NOTCH and HES1 has led to hypnotize a possible tumor suppressor role of the NOTCH signalling [103]. As confirmation of this hypothesis, Maggi et al [107] demonstrates that RBP2, a key component of the NOTCH repressor complex, is upregulated in gastrointestinal NENs and in liver metastases. Anyway, further studies are needed to confirm the role of NOTCH signalling in GI-NENs and to drive an effective therapeutic strategy modulating the NOTCH pathway in these tumour.…”
Section: Role Of Notch In Neuroendocrine Gastro-entero-pancreatic Neumentioning
confidence: 98%